JUNENILE DELINQUENCY IN GIRLS II. THE APPLICATION OF THE JESNESS INVENTORY - Polnaya, Meera
The use of the Inventory with 3 groups of girls is described—75 normal girls studying in 10th standard, 75 girls in an approved school with criminal record and 75 girls in the approved school requiring ‘care and protection’. The results indicate that most of the sub-tests of the Inventory discriminate the delinquents from the normals. The results are compared with American and British studies. The usefulness of the Inventory in an Indian Setting indicated and future research trends are identified